The width of the flux tube in SU(3) pure gauge theory - Batgerel, Munkhzaya; Chagdaa, Sodbileg; Galsandorj, Enkhtuya (Proceedings of the Mongolian Academy of Sciences, 2023)
In this paper, we present results obtained from the flux tubes between a quark and an antiquark in SU(3) pure gauge lattice field theory. We fit the transverse distribution of the energy density and the parallel components of the chromoelectric and chromomagnetic fields with several functions and used the coefficients obtained from the fit for computation of the width of the flux tube. Subsequently, we looked into in the dependence of the width of the flux tube on the distance between the static quark-antiquark sources and temperatures. Finally, we compared our results with those from other similar studies. We observed that the numerical value of the width of the flux tube computed from the pure gauge theory is larger than that from the full QCD theory, and the width of the flux tube widened until Tc, and then decreased above the critical temperature.